A longitudinal case study on the development of consonant–vowel distribution in the babbling of a Czech–English infant - Cilibrasi, Luca; Dunková, Jirina (Journal of Monolingual and Bilingual Speech, 2022)
Previous studies have shown that bilingual infants adjust the distribution of vowels and consonants, while babbling, to the languages they are exposed to, but little is known about the developmental trajectory of this skill. In this study, an infant exposed to English and Czech from birth was recorded every two/three days from the age of 0;6.13 to the age of 1;6.21 while babbling, and the distribution of vowels and consonants was analysed in his speech in relationship to the person he was interacting with. The study shows that the proportion of consonants increases throughout development in the recordings in which the child is interacting with his father (Czech speaker), and it remains instead stable over development in the recordings in which the child is interacting with his mother (English speaker). This finding suggests that the child is able to tie his babbling strategies, within a few months, to the distribution of vowels and consonants occurring in the linguistic environment.